A porous polymer electrolyte layer, a method of preparation and a battery therefor
Patent Information
- Application Number
- CN202611084378.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-21
AI Technical Summary
[0003]针对现有技术中液态电解质、固态电解质存在安全性差、电导率低以及机械强度差的问题,提供一种多孔聚合物电解质层、制备方法及其电池
本申请提供的多孔聚合物电解质层,所述有机聚合物骨架、所述导离子体混合,得到具有孔隙的多孔聚合物电解质层,多孔聚合物电解质层中引入的孔隙中可填充液态电解液或凝胶聚合物电解质,形成快速离子迁移通道,实现离子在固-液复合相中的高效传输,显著提升离子电导率,同时多孔聚合物电解质层中的有机聚合物骨架提供了机械支撑,进而抑制电极体积变化导致的界面剥离问题,同时降低枝晶穿透风险,进而达到从结构层面强化电池的安全性能;
Smart Images

Figure CN122599530B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a porous polymer electrolyte layer, its preparation method, and a battery thereof. Background Technology
[0002] With the widespread application of batteries in electric vehicles, energy storage systems, and portable electronic devices, the electrolyte, as a core component of the battery, directly affects the battery's safety, energy density, and cycle life. Traditional liquid electrolytes, while possessing good ionic conductivity (approximately 10⁻⁶), still have limitations. -2 S·cm -1 While polymer electrolytes offer improved safety and electrode wettability, their high volatility and flammability can easily trigger battery thermal runaway, posing a serious safety hazard. Solid polymer electrolytes, although offering enhanced safety, generally suffer from low room-temperature ionic conductivity (<10). -4 S·cm -1 Problems such as poor electrode / electrolyte interface contact and poor mechanical strength have suppressed ion transport dynamics and limited its commercial application. Summary of the Invention
[0003] To address the issues of poor safety, low conductivity, and poor mechanical strength in existing liquid and solid electrolytes, a porous polymer electrolyte layer, its preparation method, and its battery are provided.
[0004] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: On one hand, the present invention provides a porous polymer electrolyte layer, comprising an organic polymer framework and an ion conductor; The porous polymer electrolyte layer satisfies the following relationship: , And 10%≤φ≤90%, 0.5μm≤L≤100μm, 0.1μm≤D avg ≤20μm; Wherein, φ is the porosity of the porous polymer electrolyte layer; L represents the thickness of the porous polymer electrolyte layer, in μm. D avg The average pore size of the porous polymer electrolyte layer is expressed in μm.
[0005] Optionally, the porous polymer electrolyte layer satisfies the following relationship: .
[0006] Optionally, the thickness of the porous polymer electrolyte layer is 2μm≤L≤50μm.
[0007] Optionally, the average pore size of the porous polymer electrolyte layer is 0.3 μm ≤ D.avg ≤5μm.
[0008] Optionally, the porosity of the porous polymer electrolyte layer is 30% ≤ φ ≤ 70%.
[0009] Optionally, the maximum pore size of the porous polymer electrolyte layer is D. max D max ≤0.5L.
[0010] Optionally, the organic polymer backbone includes one or more of polyvinylidene fluoride, polyvinylidene fluoride derivatives, polyethylene oxide, polyethylene oxide derivatives, polyacrylonitrile, polyacrylonitrile derivatives, polymethyl methacrylate, and polymethyl methacrylate derivatives.
[0011] Optionally, the ion-conducting agent includes one or more of LiFSI, LiTFSI, LiPF6, LiClO4, LiBF4, LiODFB, LiBOB, LiPO2F2, LATP, LLTO, LLZO, LLZTO, LAGP, LiPON, and LGPS.
[0012] Optionally, it may also include inorganic fillers, which include one or more of LiTaO3, BaTiO3, SrTiO3, LaMnO3, PbZrO3, PbTiO3, LaFeO3, SiO2, Al2O3, TiO2, ZrO2, MgO, ZnO, CeO2, and zeolite.
[0013] Optionally, the mass ratio of the organic polymer skeleton, the ion conductor, and the inorganic filler is (3~20):(5~30):(0~12).
[0014] Optionally, the above-mentioned method for preparing the porous polymer electrolyte layer includes the following operations: An organic polymer framework, an ion conductor, an inorganic filler, and a solvent are mixed to obtain a porous polymer electrolyte slurry. The porous polymer electrolyte mixture slurry is dried, cured, and pore-forming to obtain a porous polymer electrolyte layer.
[0015] Optionally, the solvent includes two of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, tetrahydrofuran, and acetonitrile, and the boiling point difference between the two selected solvents is 30~150℃.
[0016] On the other hand, the present invention provides a battery comprising a positive electrode, a negative electrode, and the aforementioned porous polymer electrolyte layer, or a porous polymer electrolyte layer prepared by the method for preparing the aforementioned porous polymer electrolyte layer.
[0017] The non-solid electrolyte includes a liquid electrolyte or a gel electrolyte, and the non-solid electrolyte permeates into the pores of the porous polymer electrolyte layer; Optionally, the intrinsic ionic conductivity of the porous polymer electrolyte layer in the absence of a non-solid electrolyte is 0.21~0.66 mS·cm. −1 The porous polymer electrolyte layer has an ionic conductivity of 1.95~6.32 mS·cm after being permeated with a non-solid electrolyte. −1 .
[0018] The beneficial effects of this application are as follows: The porous polymer electrolyte layer provided in this application is obtained by mixing the organic polymer framework and the ion-conducting fluid to obtain a porous polymer electrolyte layer with pores. The pores introduced in the porous polymer electrolyte layer can be filled with liquid electrolyte or gel polymer electrolyte to form a fast ion migration channel, realize the efficient transport of ions in the solid-liquid composite phase, and significantly improve the ion conductivity. At the same time, the organic polymer framework in the porous polymer electrolyte layer provides mechanical support, thereby suppressing the interface peeling problem caused by electrode volume change and reducing the risk of dendrite penetration, thereby enhancing the safety performance of the battery from the structural level. Furthermore, when the porous polymer electrolyte layer meets the requirements described in this application... The relationship is as follows, and the porosity of the porous polymer electrolyte layer satisfies 10%≤φ≤90%, the thickness of the porous polymer electrolyte layer satisfies 0.5μm≤L≤100μm, and the average pore size of the porous polymer electrolyte layer is 0.1μm≤D. avg At a size ≤20μm, it is beneficial to further form a stable and highly functional structure through the synergistic mixing of the organic polymer framework and the ion-conducting material. At the same time, the specific porosity, thickness, and average pore size range and relationship limits can precisely control the pore structure, which is conducive to the dispersion of the ion-conducting material and ion transport, improves the room temperature ionic conductivity, improves the interfacial contact between the electrode or electrolyte, effectively improves the safety of the battery, further optimizes the ion conduction efficiency and interfacial stability, and thus comprehensively improves the overall electrochemical performance of the battery. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of lithium-ion transport in a porous polymer electrolyte layer provided by the present invention; Figure 2 This is a microstructure diagram of the porous polymer electrolyte layer provided in Embodiment 1 of the present invention; Figure 3 This is a microstructure diagram of the porous polymer electrolyte layer provided in Comparative Example 1 of the present invention. Detailed Implementation
[0020] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0021] This invention provides a porous polymer electrolyte layer, comprising an organic polymer framework and an ion conductor; The porous polymer electrolyte layer satisfies the following relationship: , And 10%≤φ≤90%, 0.5μm≤L≤100μm, 0.1μm≤D avg ≤20μm; Wherein, φ is the porosity of the porous polymer electrolyte layer; L represents the thickness of the porous polymer electrolyte layer, in μm. D avg The average pore size of the porous polymer electrolyte layer is expressed in μm.
[0022] It should be noted that the porosity and average pore size in this application are tested using a mercury porosimeter. That is, the porosity and pore size distribution of the porous polymer electrolyte layer are determined by the mercury porosimeter method, and the average pore size and maximum pore size can be obtained directly from the pore size distribution (GB / T 21650).
[0023] Specifically, refer to Figure 1 A schematic diagram of lithium-ion transport in a porous polymer electrolyte layer. The porous polymer electrolyte layer provided in this application is formed by mixing the organic polymer framework and the ion-conducting fluid to obtain a porous polymer electrolyte layer with pores. The pores introduced in the porous polymer electrolyte layer can be filled with liquid electrolyte or gel polymer electrolyte to form a fast ion migration channel, realize the efficient transport of ions in the solid-liquid composite phase, significantly improve ion conductivity, and at the same time, the organic polymer framework in the porous polymer electrolyte layer provides mechanical support, thereby suppressing the interface peeling problem caused by electrode volume change, and reducing the risk of dendrite penetration, thereby enhancing the safety performance of the battery from the structural level. Furthermore, when the porous polymer electrolyte layer meets the requirements described in this application... When the porosity of the porous polymer electrolyte layer meets the following conditions: 10%≤φ≤90%, the thickness of the porous polymer electrolyte layer meets the following conditions: 0.5μm≤L≤100μm, and the average pore size of the porous polymer electrolyte layer is 0.1μm≤Davg≤20μm, it is beneficial to further form a stable and highly functional structure through the synergistic mixing of the organic polymer framework and the ion-conducting agent. At the same time, the specific range of porosity, thickness, and average pore size, as well as the limitation of the relationship, can precisely control the pore structure, which is beneficial to the dispersion of the ion-conducting agent and ion transport, improves the room temperature ionic conductivity, improves the interfacial contact between the electrode or electrolyte, and thus effectively improves the safety of the battery. It further optimizes the ion conduction efficiency and interfacial stability, thereby comprehensively improving the overall electrochemical performance of the battery.
[0024] It should be noted that the path length of ion transport is directly proportional to the thickness of the porous polymer electrolyte layer. Increasing the thickness of the porous polymer electrolyte layer will linearly increase the ohmic resistance of the electrolyte and reduce the rate performance of the battery. At the same time, increasing the thickness of the porous polymer electrolyte layer will increase the proportion of inactive materials in the battery and reduce the energy density of the battery. However, if the thickness of the porous polymer electrolyte layer is too small, it will easily increase the risk of short circuit and being pierced by lithium dendrites, and the mechanical strength will be significantly reduced. Experiments have shown that when the thickness L of the porous polymer electrolyte layer is limited to the range of 0.5μm≤L≤100μm, the battery performance can be better optimized. Generally, a larger average pore size in a porous polymer electrolyte layer can better reduce ion transport resistance and improve ion conductivity; however, an excessively large average pore size may disrupt the continuity of the polymer matrix, which may reduce the effective conductive area and increase the likelihood of short circuits. The pore size distribution and connectivity determine the tortuosity (torsional curvature) of the ion transport path. A smaller average pore size will result in a higher tortuosity, which in turn increases the effective transport distance and reduces conductivity. At the same time, an excessively small pore size is not conducive to the wetting and close contact of the electrode active material, which increases the interfacial impedance. The average pore size of the porous polymer electrolyte layer is limited to 0.1 μm ≤ D. avg Within the ≤20μm range, it can better reduce ion transport resistance and improve ion conductivity; Pores are the main channels for ion migration. Higher porosity usually means lower ion transport resistance and higher ion conductivity. Pores are responsible for absorbing liquid electrolyte. The higher the porosity, the higher the liquid absorption rate, which can provide more electrolyte. However, higher porosity may reduce the mechanical strength of the battery, affecting the assembly and operational safety of the battery. Verification revealed that when the porosity of the porous polymer electrolyte layer is limited to 10%≤φ≤90%, its performance can be well optimized.
[0025] Furthermore, the porosity φ of the porous polymer electrolyte layer can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90%. The thickness L of the porous polymer electrolyte layer can be 0.5μm, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm or 100μm; The average pore size D of the porous polymer electrolyte layer avg It can be 0.1μm, 1μm, 2μm, 4μm, 5μm, 7μm, 8μm, 10μm, 12μm, 15μm, 18μm or 20μm.
[0026] In some embodiments, the porous polymer electrolyte layer satisfies the following relationship: .
[0027] Specifically, when the porous polymer electrolyte layer satisfies When this relationship is established, the control of its pore structure is more precise. This range further balances the relationship between the porosity, thickness and average pore size of the porous polymer electrolyte layer. It can ensure that the liquid electrolyte or gel polymer electrolyte filled in the pores forms a more efficient ion migration channel, further improve the room temperature ion conductivity and optimize the electrolyte interface contact. At the same time, it can provide more suitable mechanical support through the organic polymer skeleton, more effectively suppress the risk of interface peeling and dendrite penetration caused by electrode volume changes. Meanwhile, the porous structure has a more significant effect on reducing the volatility and flammability of the electrolyte, thus achieving a better balance between ion transport efficiency, structural stability and battery safety, and further improving the overall performance of the porous polymer electrolyte layer.
[0028] In some embodiments, the thickness of the porous polymer electrolyte layer is 2μm≤L≤50μm.
[0029] Specifically, when the thickness of the porous polymer electrolyte layer is within 2μm≤L≤50μm, from the perspective of ion transport, this thickness range helps to shorten the migration path of ions within the electrolyte layer and reduce the resistance to ion transport. Combined with its limited porosity and average pore size, it can more efficiently cooperate with the liquid electrolyte or gel polymer electrolyte filled in the pores to construct a fast ion migration channel and significantly improve ion conductivity. In addition, the porous polymer electrolyte layer within this thickness range ensures that the organic polymer skeleton can better suppress the interface peeling problem caused by electrode volume changes while providing mechanical support, reducing the risk of dendrite penetration. At the same time, the porous structure of this thickness can more effectively reduce the volatility and flammability of the electrolyte, better ensuring safety during battery operation, and taking into account multiple performance aspects such as ion transport efficiency, mechanical stability, and battery safety.
[0030] Specifically, in a preferred embodiment, the thickness L of the porous polymer electrolyte layer can be 2μm, 4μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm or 50μm.
[0031] In some embodiments, the average pore size of the porous polymer electrolyte layer is 0.3 μm ≤ D avg ≤5μm.
[0032] Specifically, when the average pore size of the porous polymer electrolyte layer is 0.3 μm ≤ D avg At a pore size of ≤5μm, this range of pore size ensures that liquid electrolytes or gel polymer electrolytes can be smoothly filled into the pores to construct efficient ion migration channels, facilitating more efficient ion transport in the solid-liquid composite phase and significantly improving ion conductivity. It can also work synergistically with the organic polymer framework to provide better mechanical support, suppress interfacial stripping caused by electrode volume changes, and reduce the risk of dendrite penetration. At the same time, it can effectively reduce the volatility and flammability of the electrolyte, further improving battery safety, thereby achieving a better balance between ion transport, structural stability, and battery safety performance.
[0033] In a preferred embodiment, the average pore size D of the porous polymer electrolyte layer avg It can be 0.3μm, 0.5μm, 1μm, 2μm, 3μm, 4μm or 5μm.
[0034] In some embodiments, the porosity of the porous polymer electrolyte layer is 30% ≤ φ ≤ 70%.
[0035] Specifically, when the porosity of the porous polymer electrolyte layer is 30%≤φ≤70%, the thickness and average pore size of the porous polymer electrolyte layer are combined to achieve comprehensive performance that balances ion transport, mechanical stability and safety.
[0036] In a preferred embodiment, the porosity φ of the porous polymer electrolyte layer can be 30%, 40%, 50%, 60%, or 70%.
[0037] In some embodiments, the maximum pore size of the porous polymer electrolyte layer is D. max D max ≤0.5L.
[0038] The porous polymer electrolyte layer described in this application further defines the maximum pore size D of the porous polymer electrolyte layer. maxWith a pore size of ≤0.5L, the mechanical and transport properties of the electrolyte layer can be synergistically optimized while ensuring that the porous structure provides an efficient channel for ion transport. Specifically, on the one hand, by controlling the maximum pore size to 0.5 times or less of the thickness of the porous polymer electrolyte layer, the continuity and integrity of the organic polymer skeleton can be avoided due to excessively large pore sizes. This ensures that the polymer skeleton provides sufficient mechanical support for the electrolyte layer, effectively improving the overall mechanical strength of the electrolyte layer, suppressing interfacial delamination and cracking caused by electrode volume changes during battery cycling, reducing the risk of lithium dendrite formation and penetration, and significantly improving the structural stability and safety of the battery. On the other hand, this limitation can precisely control the uniformity and connectivity of the pore structure, avoiding problems such as uneven distribution of conductive ions, local enrichment of electrolyte, or leakage and volatilization caused by local oversized pores. This makes the ion transport channels more regular and continuous, further improving ion transport efficiency and interfacial compatibility, and balancing high ionic conductivity and excellent mechanical properties. This better solves the problems of poor safety of traditional liquid electrolytes and the difficulty in balancing conductivity and mechanical strength of solid electrolytes.
[0039] In some embodiments, the organic polymer backbone includes one or more of polyvinylidene fluoride, polyvinylidene fluoride derivatives, polyethylene oxide, polyethylene oxide derivatives, polyacrylonitrile, polyacrylonitrile derivatives, polymethyl methacrylate, and polymethyl methacrylate derivatives.
[0040] Specifically, in the porous polymer electrolyte layer, the organic polymer framework is selected from one or more of polyvinylidene fluoride and its derivatives, polyethylene oxide and its derivatives, polyacrylonitrile and its derivatives, and polymethyl methacrylate and its derivatives. Polyvinylidene fluoride and its derivatives have good chemical stability and mechanical strength, which can effectively enhance the structural stability of the electrolyte layer and inhibit dendrite growth and interface peeling. Polyethylene oxide and its derivatives, with their excellent complexing ability for lithium salts due to their highly polar segments, can improve ionic conductivity. Polyacrylonitrile and its derivatives have excellent film-forming properties and thermal stability, which helps to reduce the flammability of the electrolyte. Polymethyl methacrylate and its derivatives can optimize the interfacial compatibility between the electrolyte layer and the electrode. When the organic polymer framework described in this application is used alone or in combination with other materials, each of the above-mentioned materials can fully leverage its respective performance advantages, improve the performance of the porous polymer electrolyte layer, and meet the diverse needs of electrolytes in battery applications.
[0041] In some embodiments, the ion-conducting agent includes one or more of LiFSI, LiTFSI, LiPF6, LiClO4, LiBF4, LiODFB, LiBOB, LiPO2F2, LATP, LLTO, LLZO, LLZTO, LAGP, LiPON, and LGPS.
[0042] Specifically, by limiting the ion conductor to one or more of LiFSI, LiTFSI, LiPF6, LiClO4, LiBF4, LiODFB, LiBOB, LiPO2F2, LATP, LLTO, LLZO, LLZTO, LAGP, LiPON, and LGPS, and relying on the high lithium-ion migration capacity and chemical stability of different types of lithium salts and inorganic solid-state ion conductors, and matching them with the organic polymer framework, it can be uniformly dispersed inside the porous polymer electrolyte layer. By constructing a continuous and stable long-range ion transport pathway through the controllable pore structure within the layer, it can improve the lithium-ion conduction rate and room-temperature ion conductivity. It can also optimize the overall oxidation resistance, thermal stability, and decomposition resistance of the electrolyte, reduce electrolyte side reaction corrosion, improve electrode-electrolyte interface compatibility, inhibit lithium dendrite growth, alleviate volume deformation and interface peeling problems during electrode cycling, and further improve the electrolyte ion conduction efficiency, interface stability, and safety, thereby effectively improving the battery rate performance and cycle life.
[0043] Furthermore, as described above, the aforementioned ion-conducting materials can dissociate to provide sufficient free lithium ions, reduce the ion migration energy barrier, and enhance the bulk ion conductivity of the electrolyte. They also possess excellent electrochemical stability and temperature resistance, and can suppress electrolyte decomposition side reactions. Among these, LLTO, LiPON, and LGPS components can optimize interfacial impedance; organic lithium salts such as LiFSI and LiTFSI have low hygroscopicity and good thermal stability, effectively reducing the risk of electrolyte decomposition and improving battery safety. Moreover, the lithium ions dissociated in the polymer matrix have high transference numbers, promoting efficient ion transport; LiPF6 and LiClO4 have high ion transference numbers... High ionic conductivity enables rapid lithium-ion conduction, enhancing battery charge and discharge performance. Inorganic solid electrolyte conductors such as LATP, LLZO, LLZTO, and LAGP possess continuous lithium-ion lattice transport channels with fast ion migration rates and high mechanical strength. They can be interspersed within the porous structure of the polymer framework, constructing a multidimensional composite ion transport network. Combining them with organic lithium salts can create complementary advantages, significantly improving room-temperature ionic conductivity, enhancing the interfacial stability between the electrode and electrolyte, and suppressing lithium dendrite growth. This, in turn, improves the overall performance of the porous polymer electrolyte layer from multiple dimensions, including ion conduction efficiency, battery safety, and cycle stability.
[0044] In some embodiments, the invention further includes inorganic fillers, which include one or more of the following: LiTaO3, BaTiO3, SrTiO3, LaMnO3, PbZrO3, PbTiO3, LaFeO3, SiO2, Al2O3, TiO2, ZrO2, MgO, ZnO, CeO2, and zeolite.
[0045] Specifically, LiTaO3 and BaTiO3 have high dielectric constants, which can effectively promote the dissociation of lithium salts, increase lithium ion concentration, and improve ionic conductivity. Perovskite dielectric fillers such as PbTiO3, SrTiO3, and PbZrO3 can increase the concentration of free lithium ions and improve the polarization phenomenon at the electrolyte interface due to their high dielectric constant. LaMnO3 and LaFeO3 rare earth-based oxides exhibit excellent chemical stability, which can suppress side reactions at the electrode interface and buffer structural deformation during cycling. SiO2 and Al2O3 nanoparticles dispersed in the polymer matrix can enhance the mechanical strength of the electrolyte layer, inhibit lithium dendrite penetration, and improve structural stability. TiO2 and ZrO2 have good chemical stability, which can optimize the electrolyte-electrode interface contact and reduce interfacial impedance. MgO and ZnO have good alkaline adsorption properties, which can capture acidic impurities produced by electrolyte decomposition and slow down corrosion and degradation. CeO2 has excellent antioxidant and oxygen buffering properties, which can improve the high-temperature tolerance and cycle stability of electrolytes. The unique porous structure and ion exchange properties of zeolites help to uniformly disperse lithium salts, regulate ion migration pathways, and improve ion transport kinetics. These inorganic fillers, individually or in synergy, can optimize the performance of the electrolyte layer in many aspects, such as ion conduction, mechanical properties, and interface stability, helping batteries achieve higher safety and longer cycle life.
[0046] In some embodiments, the mass ratio of the organic polymer skeleton, the ion conductor, and the inorganic filler is (3~20):(5~30):(0~12).
[0047] The mass ratio range of the above-mentioned organic polymer skeleton, the ion-conducting agent and the inorganic filler can achieve synergistic effect of each component; Specifically, the dominant organic polymer backbone ensures the basic structural integrity and mechanical support of the electrolyte layer; the proportion of ion-conducting agents meets the ion conduction requirements, ensuring efficient lithium-ion migration; and the appropriate addition of inorganic fillers can fully leverage their role in enhancing mechanical properties and optimizing interface characteristics without affecting the matrix structure, thereby achieving a balance between structural stability, ion transport efficiency, and comprehensive electrochemical performance, further improving the overall performance of the porous polymer electrolyte layer.
[0048] In some embodiments, the method for preparing the porous polymer electrolyte layer described above includes the following operations: An organic polymer framework, an ion conductor, an inorganic filler, and a solvent are mixed to obtain a porous polymer electrolyte slurry. The porous polymer electrolyte mixture slurry is dried, cured, and pore-forming to obtain a porous polymer electrolyte layer.
[0049] Specifically, the preparation method of the above-mentioned porous polymer electrolyte layer is carried out as follows: Organic polymer framework, ion conductor, inorganic filler and solvent were ball-milled at 500 rpm for 2 hours to obtain a porous polymer electrolyte slurry. The porous polymer electrolyte layer is prepared by casting. The mixed slurry of porous polymer electrolyte is poured into a mold and dried at 60°C for 24 hours.
[0050] Specifically, the aforementioned porous polymer electrolyte layer can be made into a self-supporting membrane or coated on the surface of a separator or electrode. There are no restrictions on the carrier supporting the electrolyte layer, as long as its introduction into the battery does not affect the normal operation of the battery.
[0051] On the one hand, the voids formed in the porous polymer electrolyte layer can be filled with substances capable of transporting lithium ions, including but not limited to conventional solutions, gel polymers, and other substances.
[0052] Although porous polymer electrolytes reduce the solid-phase transport path of lithium ions, the electrolyte filling the pores provides a liquid-phase transport path for lithium ions. Since the liquid-phase transport rate is much higher than the solid-phase transport rate, the ion transport rate is greatly improved. Compared with porous polymer electrolytes, non-porous polymer electrolytes can only transport lithium ions through the polymer electrolyte layer, resulting in a slow ion transport rate (solid-phase transport).
[0053] It should be noted that when the pores of the porous polymer electrolyte layer are not filled with a material capable of transporting lithium ions, the ionic conductivity σ of the porous polymer electrolyte layer must satisfy σ≥0.01mS·cm. -1 For porous polymer electrolyte layers whose pores are filled with substances capable of transporting lithium ions, the ionic conductivity σ' must satisfy σ'≥1mS·cm. -1 .
[0054] On the other hand, pore-forming methods include, but are not limited to, solution methods, pore-forming agent methods, thermally induced phase separation methods, airflow methods, stretching pore-forming methods, and laser methods. Specifically, the solution method involves dissolving the polymer in a mixture of two solvents with different boiling points. During the drying process, the lower-boiling-point solvent evaporates preferentially. As the solvent evaporates, the polymer begins to precipitate, forming a polymer-rich region (the future framework of the polymer electrolyte layer) and a polymer-poor region (rich in solvent). Finally, as the higher-boiling-point solvent completely evaporates, the space it originally occupied is retained, forming a porous structure. Pore-forming agent method: Inorganic salts (such as NaCl, CaCO3), small organic molecules (such as sucrose, PEG) or volatile substances that are insoluble in polymer solvents are mixed into the polymer solution as pore-forming agent powders. After film formation, the pore-forming agent is removed by washing or sublimation, leaving pores. Thermally induced phase separation: The polymer is dissolved in a high-boiling-point diluent (such as paraffin oil) to form a homogeneous solution at high temperature. Then, by cooling, liquid-liquid or solid-liquid phase separation occurs, forming a polymer-rich phase and a diluent-rich phase. Finally, the diluent is removed by extraction or drying, and the spaces previously occupied by the diluent form a porous structure. Airflow method: Before the porous polymer electrolyte layer is formed (during the slurry drying process), gas is blown into it to create pores; Stretch-induced pore method: First, a non-porous semi-crystalline polymer electrolyte layer is prepared, and then micropores are formed by unidirectional or bidirectional stretching to cause the interface between the crystalline and amorphous regions to peel off. Laser method: The polymer electrolyte layer is irradiated with a laser to form through holes.
[0055] In some embodiments, the solvent includes two of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), tetrahydrofuran (THF), and acetonitrile (ACN), and the boiling point difference between the two selected solvents is 30~150°C.
[0056] It should be noted that, although several solvents are listed above, in the preparation of the porous polymer electrolyte layer, the two solvents selected in this application need to have a boiling point difference of 30~150℃ between them. If the boiling point difference between the two selected solvents is too large (exceeding 150°C), it can easily cause structural runaway. After the relatively low-boiling-point solvent evaporates in the first step, the remaining high-boiling-point solvent will form enriched droplets. The enriched droplets will merge and expand like oil droplets in water, eventually forming irregular large cavities, and even causing the pore walls to rupture. As the pore-forming droplets are excessively expanded, the surrounding polymer matrix becomes thinner, and the mechanical strength drops sharply. In the final drying stage, these weak pore walls cannot resist capillary pressure, causing the entire porous structure to collapse inward, and the final result may be a dense film. If the boiling point difference is too small (below 30℃), when the low-boiling-point solvent evaporates, the relatively high-boiling-point solvent will inevitably evaporate along with it due to the small boiling point difference, and cannot be retained separately, thus making it impossible to create pores.
[0057] Specifically, when N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) are combined to prepare a solvent, compared to DMF, DMSO, with its high boiling point and strong solubility, can slowly regulate the phase separation rate during the slurry solidification process, making the pore structure more uniform and controllable. Compared to DMSO, DMF, with its lower boiling point and good volatility, can accelerate the solvent removal process. The synergistic effect of DMF and DMSO can better regulate the pore morphology, thereby obtaining ideal pore size and porosity. That is, by using any two solvents with a boiling point difference of 30~150℃ to prepare a solvent, it is possible to ensure that the organic polymer skeleton, ion conductor and inorganic filler are fully dispersed, and to induce the formation of efficient ion transport channels through phase separation, thereby improving the ionic conductivity of the electrolyte layer. At the same time, it optimizes the mechanical properties and electrode interface contact, thereby enhancing the safety and stability of the battery.
[0058] In another embodiment, the present invention provides a battery comprising a positive electrode, a negative electrode, and the aforementioned porous polymer electrolyte layer, or a porous polymer electrolyte layer prepared by the method for preparing the aforementioned porous polymer electrolyte layer.
[0059] Specifically, the battery includes the porous polymer electrolyte layer described in this application. The organic polymer framework and the ion-conducting fluid are mixed to obtain a porous polymer electrolyte layer with pores. The pores introduced in the porous polymer electrolyte layer can be filled with liquid electrolyte or gel polymer electrolyte to form a fast ion migration channel, realize the efficient transport of ions in the solid-liquid composite phase, and significantly improve the ion conductivity. At the same time, the organic polymer framework in the porous polymer electrolyte layer provides mechanical support, thereby suppressing the interface peeling problem caused by electrode volume change and reducing the risk of dendrite penetration. Furthermore, when the porous polymer electrolyte layer meets the requirements described in this application... The relationship is as follows, and the porosity of the porous polymer electrolyte layer satisfies 10%≤φ≤90%, the thickness of the porous polymer electrolyte layer satisfies 0.5μm≤L≤100μm, and the thickness of the porous polymer electrolyte layer is 0.1μm≤D. avg When the diameter is ≤20μm, it is beneficial to further form a stable and highly functional structure through the synergistic mixing of organic polymer framework and ion conductor. At the same time, the specific porosity, thickness and average pore size range and relationship can be limited to precisely control the pore structure, which is beneficial to the dispersion of ion conductor and ion transport, improves room temperature ionic conductivity, improves the interfacial contact of electrode or electrolyte, and thus effectively improves battery safety.
[0060] In some embodiments, the non-solid electrolyte includes a liquid electrolyte or a gel electrolyte, and the non-solid electrolyte permeates into the pores of the porous polymer electrolyte layer; The intrinsic ionic conductivity of the porous polymer electrolyte layer without the addition of a non-solid electrolyte is 0.21~0.66 mS·cm. -1 The porous polymer electrolyte layer has an ionic conductivity of 1.95~6.32 mS·cm after being permeated with a non-solid electrolyte. -1 .
[0061] Specifically, porous polymer electrolytes rely solely on the synergistic action of the organic polymer framework and the ion-conducting fluid in a two-phase solid state to achieve ion conduction. Ion migration paths are constrained by factors such as limited polymer chain movement and interfacial impedance between ion-conducting fluid particles. Therefore, without the addition of a non-solid electrolyte, the intrinsic ionic conductivity of the material remains between 0.21 and 0.66 mS·cm. -1 interval; When the non-solid electrolyte permeates into the porous polymer electrolyte layer and connects the pores, the original air phase in the pores is replaced by the non-solid electrolyte with a high ion migration rate. This creates a high-speed solid-liquid composite ion-conducting channel within the three-dimensional continuous pore network formed by the polymer skeleton. On one hand, the liquid electrolyte significantly weakens the interfacial contact resistance between the solid-phase ion-conducting particles and avoids the conductivity bottleneck caused by insufficient low-temperature movement of polymer chain segments. On the other hand, the rigid organic polymer skeleton continuously provides spatial support. This synergistic effect, leveraging the conductivity advantages of both solid and liquid phases, increases the ionic conductivity of the composite electrolyte after permeation with the non-solid electrolyte to 1.95~6.32 mS·cm. -1 .
[0062] The present invention will be further illustrated by the following examples.
[0063] Table 1
[0064] Example 1 This embodiment illustrates the porous polymer electrolyte layer, its preparation method, and the battery disclosed in this invention, and includes the following steps: 8g of organic polymer backbone (PVDF) was dissolved in 100g of DMF solvent, and then 12g of ion conductor (LiFSI), 5g of inorganic filler LATP, 2g of Al2O3, 1g of LiTaO3 and 100g of DMSO solvent were added. The mixture was ball-milled at 500rpm for 2h to obtain a mixed slurry of porous polymer electrolyte. Using a casting method, a mixture of porous polymer electrolytes is poured into a mold and dried and cured at 60°C for 24 hours to obtain a porous polymer electrolyte layer. The porous polymer electrolyte layer has a porosity of 68.2%, a thickness of 42 μm, and an average pore size of 3.54 μm.
[0065] Battery manufacturing Preparation of the positive electrode: The positive electrode active material (high-nickel ternary), conductive agent (CNT), and binder (PVDF) were thoroughly mixed in NMP solvent at a weight ratio of 97:1.5:1.5 to obtain the positive electrode slurry. The positive electrode slurry is uniformly coated onto aluminum foil, and then processed through drying, cold pressing, slitting, sheet making, welding tabs, and adhesive application to obtain the positive electrode.
[0066] Preparation of negative electrode: The negative electrode active material graphite, conductive agent carbon black, binder styrene-butadiene rubber, and sodium carboxymethyl cellulose were thoroughly mixed in deionized water at a weight ratio of 94:2:2:2 to obtain the negative electrode slurry. The negative electrode slurry is uniformly coated onto copper foil, and then the negative electrode is obtained through processes such as drying, cold pressing, slitting, sheet making, welding tabs, and applying adhesive.
[0067] Cell manufacturing: The positive electrode, porous polymer electrolyte layer, and negative electrode are stacked in sequence, with the porous polymer electrolyte layer in the middle of the positive and negative electrodes and the positive electrode in the center of the negative electrode. The cells are obtained by stacking these layers.
[0068] Assemble the battery: The battery is obtained by welding tabs, packaging, baking and drying, injecting electrolyte and fully wetting it, vacuum sealing, formation, and final sealing.
[0069] Examples 2-11 Examples 2-11 illustrate the porous polymer electrolyte layer, the preparation method of the porous polymer electrolyte layer, and the battery disclosed in this invention, and include most of the operations in Example 1, except that: In the preparation of porous polymer electrolyte mixed slurry, different proportions of DMSO are added to create pores to varying degrees. The porosity, thickness (μm), and average pore size (μm) of the obtained porous polymer electrolyte layer are shown in Table 1.
[0070] Example 12 Example 12 illustrates the porous polymer electrolyte layer, the preparation method of the porous polymer electrolyte layer, and the battery thereof disclosed in this invention. It includes most of the operations in Example 1, except that: 8g of organic polymer backbone (PVDF) was dissolved in 100g of DMF solvent, and then 12g of ion-conducting agent (LiFSI), 5g of inorganic filler LATP, 2g of Al2O3, 1g of LiTaO3 and 100g of THF solvent were added. The mixture was ball-milled at 500rpm for 2h to obtain a mixed slurry of porous polymer electrolyte. Using a casting method, a mixture of porous polymer electrolytes is poured into a mold and dried and cured at 60°C for 24 hours to obtain a porous polymer electrolyte layer.
[0071] Comparative Examples 1-5 Comparative Examples 1-5 are used to compare and illustrate the porous polymer electrolyte layer, the preparation method of the porous polymer electrolyte layer, and the battery disclosed in this invention. They include most of the operations in Example 1, but differ in that: The porosity, thickness (μm), and average pore size (μm) of the obtained porous polymer electrolyte layer are shown in Table 1.
[0072] Performance testing The following performance tests were performed on Examples 1-12 and Comparative Examples 1-5 prepared above: 1. The microstructure of the porous polymer electrolyte layers prepared in Example 1 and Comparative Example 1 was examined, and the results were obtained respectively. Figure 2 as well as Figure 3 .
[0073] Figure 2 The porous polymer electrolyte layer microstructure prepared in Example 1 of this application is composed of... Figure 2 It can be seen that its porosity, thickness and average pore size are all within the preferred range defined by the present invention, thus obtaining uniform pore distribution, good connectivity and regular pore size, which can provide a stable and smooth channel for ion transport, while ensuring the mechanical strength of the electrolyte layer. Figure 3 The microstructure of Comparative Example 1 has a porosity that does not meet the limits defined in this application. Figure 3 It can be seen that the overall number of pores is sparse and unevenly distributed, making it difficult to form efficient ion transport pathways, which is different from Example 1. Figure 2 The comparison provides a clear contrast, thus verifying that the limitations of this application on the range and relationship of porosity, thickness, and average pore size can effectively control the pore structure, promote the dispersion of conductive ions and ion transport, and thereby improve the safety of the battery.
[0074] 2. Ionic conductivity test A double stainless steel sheet blocking battery system was assembled using coin cells, with stainless steel sheets as the positive electrode and stainless steel sheets as the negative electrode. The porous polymer electrolyte layer prepared in the above embodiments and comparative examples was used as the separator to fabricate coin cells. The coin cell was subjected to EIS testing using an electrochemical workstation with a frequency range of 0.1 Hz to 100 kHz and a voltage amplitude of 0.005 V. The test results were plotted as a Nyquist plot. A straight line was fitted to the high-frequency data points and extrapolated to intersect the real axis. The real part (Z') corresponding to the intersection point is the bulk resistance R of the porous polymer electrolyte layer. The ionic conductivity σ of the porous polymer electrolyte layer was calculated using the following formula. σ = L / (R*A); Where σ is the ionic conductivity of the porous polymer electrolyte layer; L is the thickness of the porous polymer electrolyte layer; A is the effective contact area between the porous polymer electrolyte layer and the blocking electrode (stainless steel sheet); and R is the volume resistance of the porous polymer electrolyte layer.
[0075] In preparing the above-mentioned coin cell, the porous polymer electrolyte layer without lithium-ion transport material in the pores was replaced with a porous polymer electrolyte layer with lithium-ion transport material pre-filled in the pores. The above test steps were repeated to obtain the ionic conductivity σ'.
[0076] 3. Ratio Test The battery prepared above was charged at 0.5C in the range of 2.5-4.25V and 25±2℃, left to stand for 10 minutes, and then discharged at 0.5C. The discharge capacity at the 0.5C rate was recorded.
[0077] 4. Cyclic stability test After being left to stand at 25±2℃ for 2 hours, the battery is subjected to standard charge-discharge cycles at a cycle rate of 0.5C and a charging voltage of 2.5-4.25V. The capacity retention rate of the battery after the cycles is calculated.
[0078] The calculation formula is as follows: Capacity retention rate after nth cycle (%) = (Discharge capacity after nth cycle) / (Discharge capacity after first cycle) * 100%.
[0079] The test results are entered into Table 2.
[0080] Table 2
[0081] As can be seen from the test results in Table 2, compared with the comparative examples, the porous polymer electrolyte layers in Examples 1-12 provided in this application all meet the requirements defined in this application. And 10%≤φ≤90%, 0.5μm≤L≤100μm, 0.1μm≤D avgAt a depth of ≤20μm, the ionic conductivity σ and σ' are both high, resulting in better discharge capacity and cycle capacity retention compared to the control. This is because the pore structure of the electrolyte layer is precisely controlled, which ensures that the liquid electrolyte or gel polymer electrolyte filled in the pores forms a more efficient ion migration channel, improves ionic conductivity and optimizes electrolyte interface contact, achieving lower impedance and thus better rate capability and cycle performance.
[0082] Furthermore, the porosity φ, thickness L, and average pore size D of the porous polymer electrolyte layers in Examples 1-5 are further specified. avg When the relationship between the three factors satisfies the preferred range further defined in this application, the ionic conductivity σ and σ' are both the highest, and the corresponding discharge specific capacity and cycle capacity retention are also higher. Porosity φ, thickness L, and average pore size D in the porous polymer electrolyte layers of Examples 6-9 avg When the relationship between these three factors only partially satisfies the preferred range, although they still exhibit high ionic conductivity σ and σ', the excessively high porosity (Example 6) and excessively large pore size (Example 9) can easily lead to local current concentration, poor interfacial contact, and unstable electrolyte layer structure, affecting ionic conductivity and subsequent cycling performance. On the other hand, excessively low porosity and excessively small pore size (Example 7) can lead to unconnected pore structures or excessively narrow pores, resulting in obstruction of the formed high-efficiency ion channels, thereby reducing ionic conductivity and increasing impedance. At the same time, excessive thickness (Examples 8 and 9) will also directly increase impedance and make it difficult to form a continuous ion transport channel, further increasing impedance. In Examples 10-11, the porosity φ, thickness L, and average pore diameter D are... avg The relationship between these three factors does not meet the preferred range defined in this application. Correspondingly, the ionic conductivity σ and σ' are low. Although appropriate control of the pore structure can form some ion migration channels and improve ionic conductivity, excessively high porosity (Example 10) and excessively small pore size (Example 11) will lead to the pore structure being unconnected or the pores being too narrow, resulting in the obstruction of the formed high-efficiency ion channels, making it impossible to achieve high ionic conductivity and low impedance, resulting in poor capacity utilization and cycle performance of the battery. Although the overall test performance in Examples 6 to 11 is inferior to that in Examples 1 to 5, the test results of each performance are still better than the comparative examples.
[0083] In Example 12, a combination of DMF and THF was used as the solvent. Compared with the combination of DMF and DMSO used in Example 1, the solvent in Example 12 has a larger boiling point difference (the boiling point difference is still within the range defined in this application). Consequently, the pores of the porous polymer electrolyte layer prepared in Example 12 are also larger. Through comparison, it was found that the pores formed in Example 12 are closer to those in Example 9 in terms of porosity and pore size. Further testing revealed that the two are also quite similar in terms of battery performance such as ionic conductivity σ, ionic conductivity σ', discharge capacity, and cycle capacity retention. Among Comparative Examples 1-5, Comparative Example 3 has a porosity of only 3.6% and an average pore size of 0.04 μm, which are far below the lower limit specified in this application. It has few pores, small pore size, and poor pore connectivity, resulting in insufficient space to accommodate the electrolyte. This makes it impossible to construct a continuous and efficient liquid-phase ion transport pathway, leading to high solid-phase ion conduction resistance. Consequently, its ionic conductivity σ is only 0.03 mS·cm. -1 After being immersed in the electrolyte, the conductivity σ' is only 0.21 mS·cm. -1 The obstruction of ion transport resulted in a low discharge capacity of 163.2 mAh / g, with a capacity retention rate of only 56.3% after 200 cycles, indicating severe cycle degradation. The excessively high porosity of Comparative Example 4 and the excessively large pore size of Comparative Example 2 can easily lead to localized current concentration, poor interfacial contact, and unstable electrolyte layer structure, affecting ionic conductivity and subsequent cycling performance. Furthermore, the excessive thickness of Comparative Examples 2 and 4 directly increases impedance and makes it difficult to form a continuous ion transport channel, further increasing impedance.
[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A porous polymer electrolyte layer, characterized in that, Includes organic polymer framework and ion conductor; Porous polymer electrolytes satisfy the following relationship: , And 10%≤ ≤90%, 0.5μm≤L≤100μm, 0.1μm≤D avg ≤20μm; in, The porosity of the porous polymer electrolyte layer; L represents the thickness of the porous polymer electrolyte layer, in μm. D avg The average pore size of the porous polymer electrolyte layer is expressed in μm.
2. The porous polymer electrolyte layer according to claim 1, characterized in that, The porous polymer electrolyte layer satisfies the following relationship: 。 3. The porous polymer electrolyte layer according to claim 1, characterized in that, The thickness of the porous polymer electrolyte layer is 2μm≤L≤50μm.
4. The porous polymer electrolyte layer according to claim 1, characterized in that, The average pore size of the porous polymer electrolyte layer is 0.3 μm ≤ D avg ≤5μm.
5. The porous polymer electrolyte layer according to claim 1, characterized in that, The porosity of the porous polymer electrolyte layer is ≤30%. ≤70%.
6. The porous polymer electrolyte layer according to claim 1, characterized in that, The maximum pore size of the porous polymer electrolyte layer is D. max D max ≤0.5L.
7. The porous polymer electrolyte layer according to claim 1, characterized in that, The organic polymer backbone includes one or more of polyvinylidene fluoride, polyvinylidene fluoride derivatives, polyethylene oxide, polyethylene oxide derivatives, polyacrylonitrile, polyacrylonitrile derivatives, polymethyl methacrylate, and polymethyl methacrylate derivatives.
8. The porous polymer electrolyte layer according to claim 1, characterized in that, The ion-conducting agent includes one or more of LiFSI, LiTFSI, LiPF6, LiClO4, LiBF4, LiODFB, LiBOB, LiPO2F2, LATP, LLTO, LLZO, LLZTO, LAGP, LiPON, and LGPS.
9. The porous polymer electrolyte layer according to claim 1, characterized in that, It also includes inorganic fillers, which include one or more of LiTaO3, BaTiO3, SrTiO3, LaMnO3, PbZrO3, PbTiO3, LaFeO3, SiO2, Al2O3, TiO2, ZrO2, MgO, ZnO, CeO2, and zeolite.
10. The porous polymer electrolyte layer according to claim 9, characterized in that, The mass ratio of the organic polymer skeleton, the ion conductor and the inorganic filler is (3~20):(5~30):(0~12).
11. The method for preparing a porous polymer electrolyte layer according to any one of claims 1-10, characterized in that, Includes the following operations: An organic polymer framework, an ion conductor, an inorganic filler, and a solvent are mixed to obtain a porous polymer electrolyte slurry. The porous polymer electrolyte mixture slurry is dried, cured, and pore-forming to obtain a porous polymer electrolyte layer.
12. The method for preparing a porous polymer electrolyte layer according to claim 11, characterized in that, The solvent includes two of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, tetrahydrofuran, and acetonitrile, and the boiling point difference between the two selected solvents is 30~150℃.
13. A battery, characterized in that, The porous polymer electrolyte layer includes a positive electrode, a negative electrode, and the porous polymer electrolyte layer as described in any one of claims 1-10, or the porous polymer electrolyte layer prepared by the method described in any one of claims 11-12.
14. The battery according to claim 13, characterized in that, It also includes a non-solid electrolyte, which includes a liquid electrolyte or a gel electrolyte, and the non-solid electrolyte permeates into the pores of the porous polymer electrolyte layer; The intrinsic ionic conductivity of the porous polymer electrolyte layer without the addition of a non-solid electrolyte is 0.21~0.66 mS·cm. -1 The porous polymer electrolyte layer has an ionic conductivity of 1.95~6.32 mS·cm after being permeated with a non-solid electrolyte. -1 .
Citation Information
Patent Citations
Composite porous membrane, preparation method, battery and electric equipment
CN120613548A
Composite solid electrolyte layer, preparation method and application
CN121565923A